2017
DOI: 10.1016/j.egypro.2017.03.1133
|View full text |Cite
|
Sign up to set email alerts
|

On the Possibility of CFD Modeling of the Indoor Environment in a Vehicle

Abstract: International audiencePrediction of thermal conditions inside a vehicle cabin is still a challenge due to the fast transient behaviour of physical factors influencing the boundaries of the vehicular space. In order to gain knowledge and to propose new models of air flow and thermal characteristics on one hand and new adapted thermal comfort indices on the other hand, researchers need to perform parametric studies. In this case a CFD model can be a very powerful tool which let us simulate the environmental cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 4 publications
0
18
0
Order By: Relevance
“…In this paper the effect of the driver presence and different angles of airflow from an air vent, over the thermal sensation was investigated. In previous papers [16,17], we presented the setup of the model of a cabin car and we showed that we can reproduce the in-cabin environment without passengers, finding values of indoor thermal variables from the CFD model that were similar to those of experimental measurements. We present in this article, results obtained for the air vent located on the dashboard at the driver's position (left side air vent).…”
Section: Introductionmentioning
confidence: 73%
“…In this paper the effect of the driver presence and different angles of airflow from an air vent, over the thermal sensation was investigated. In previous papers [16,17], we presented the setup of the model of a cabin car and we showed that we can reproduce the in-cabin environment without passengers, finding values of indoor thermal variables from the CFD model that were similar to those of experimental measurements. We present in this article, results obtained for the air vent located on the dashboard at the driver's position (left side air vent).…”
Section: Introductionmentioning
confidence: 73%
“…General thermal comfort index (GTCI) serves the purpose by specifying target and global values, a detailed description can be found in [32]. The global value for the predicted mean vote, PMV G , mPMV G and equivalent temperature EQT G defined by Equations (17)- (19) expresses how close we are to the thermally neutral conditions. Computing these values we could predict whether the comfort has been achieved or not.…”
Section: %mentioning
confidence: 99%
“…A review of all the factors affecting the thermal comfort inside a vehicle cabin was performed by Simion et al [18] by dividing it into measurable and personal factors. A number of CFD studies have been performed in an attempt to numerically evaluated the car thermal environment [19]. A numerical parametric study for various geometrical parameters affecting the passenger thermal environment was conducted by Currle and Maue [20].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the literature review, it was found out that researchers focused their attention on motorization and HVAC systems mainly for automobile cabins, for example [2], [3], [4], [5], [6], [7]. For the railway industry, CFD simulation tend to focus on airflow simulations in carriages, for example [8], [9].…”
Section: Introductionmentioning
confidence: 99%